Greetings commemorating the 70th anniversary of the liberation of Belgrade in World War II - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Greetings commemorating the 70th anniversary of the liberation of Belgrade in World War II